Intersensory redundancy impedes face recognition in 12-month-old infants - Bursalıoğlu, Aslı; Michalak, Alexandria; Guy, Maggie W. (Frontiers in Psychology, 2023)
This study examined the role of intersensory redundancy on 12-month-old infants' attention to and processing of face stimuli. Two experiments were conducted. In Experiment 1, 72 12month-olds were tested using an online platform called Lookit. Infants were familiarized with two videos of an actor reciting a children's story presented simultaneously. A soundtrack either matched one of the videos (experimental condition) or neither of the videos (control condition). Visual-paired comparison (VPC) trials were completed to measure looking preferences for the faces presented synchronously and asynchronously during familiarization and for novel faces. Neither group displayed looking preferences during the VPC trials. It is possible that the complexity of the familiarization stimuli made the modality-specific face properties difficult to process. In Experiment 2, infants were familiarized with the video of only one actor presented either synchronously or asynchronously with the soundtrack.Following familiarization, participants completed a VPC procedure including the familiar face and a novel face. Results from Experiment 2 showed that infants in the synchronous condition paid more attention during familiarization than infants in the asynchronous condition. Infants in the asynchronous condition demonstrated recognition of the familiar face. These findings suggest that the competing face stimuli in the Experiment 1 were too complex for the facial characteristics to be processed. The procedure in Experiment 2 led to increased processing of the face in the asynchronous presentation. These results indicate that intersensory redundancy in the presentation of synchronous audiovisual faces is very salient, discouraging the processing of modality-specific visual properties. This research contributes to the understanding of face processing in multimodal contexts, which have been understudied, although a great deal of naturalistic face exposure occurs multimodally.